Measles Vaccination Supports Millennium Development Goal 4: Increasing Coverage and Increasing Child Survival in Northern Ghana, 1996–2012 - Welaga, Paul; Hodgson, Abraham; Debpuur, Cornelius; Aaby, Peter; Binka, Fred; Azongo, Daniel; Oduro, Abraham (Frontiers in Public Health, 2018)
Background Measles vaccine (MV) administered as the last vaccine after the third dose of diphtheria-tetanus-pertussis (DTP) may be associated with better child survival unrelated to prevention of measles infection. Other studies have shown that MV administered after DTP was more beneficial and was associated with lower mortality compared with DTP administered after MV or DTP administered simultaneously with MV. We compared the difference in mortality between measles vaccinated after DTP3 and measles-unvaccinated children in Navrongo, Ghana. Methods This was a follow-up study involving annual cohort of children aged 9–23 months from 1996 to 2012. We assessed survival in relation to the measles vaccination status within the first 12 months from interview date and until 5 years of age using Cox proportional hazards models. Results In all, 38,333 children were included in the study. The proportion of children vaccinated with MV-after-DTP3 increased from 45% in 1996 to 95% in 2012. The adjusted hazard ratio (HR) for measles unvaccinated compared with MV-after-DTP3 vaccinated children was 1.38 (1.15–1.66) in the first 12 months after assessment of vaccination status and 1.22 (1.05–1.41) with follow-up to 5 years of age. The national immunization days campaigns with oral polio vaccine or MV might have reduced the effect of being MV-after-DTP3 vaccinated vs MV-unvaccinated. For 12 months of follow-up, the HR before a campaign for MV-unvaccinated children was 1.63 (1.23–2.17) compared to those who received MV-after-DTP3. After the campaign, the HR reduced to 1.23 (0.97–1.54). Stratifying the analysis by sex, measles-unvaccinated boys had a HR of 1.69 (1.33–2.61) compared to measles-unvaccinated girls who had a HR 1.06 (0.79–1.40) during 1-year follow-up. In 1989, only 7% of children in the area had received MV-after-DTP3; the increase in MV-after-DTP3 coverage from 1989 to 2012 may have lowered mortality rate among children aged 9 months to 3 years by 24%. Conclusion Though an observational study, our findings suggest that measles vaccination, administered in the recommended sequence, is associated with improved child survival and may have contributed importantly to the mortality decline toward the achievement of Millennium Development Goal 4.